Oxytocin Massage and Breastfeeding on Demand in the Uterine Involution Process - Ayu Endang Purwati Ayu; Hani Septiani; Sri Wulan Ratna Dewi; Metty Nurherliyany; Marcella Divilda; Shinta Gumilar; Gracea Petricka (Genius Midwifery Journal, 2022)
Introduction: Involution begins as soon as the placenta is delivered. During uterine involution, the uterus will return to its pre-pregnancy state and (estimated) size. Aim: The aim of this case study is to carry out comprehensive midwifery care to support maternity women the normal process of uterine involution includes IMD, oxytocin massage, and on demand breastfeeding. Method: This research method is a case report of midwifery care. The subjects in this study were mothers who gave birth at the Independent Midwife Practice as many as 3 people. Results: Correct breastfeeding techniques on demand because on-demand breastfeeding helps produce contractions by releasing the hormone oxytocin Conclusion: Uterine involution progressed well until the 7th day postpartum, this was supported by a good process starting from the IMD process after the baby was born, followed by early mobilization, direct breastfeeding, and oxytocin massage.